Research for modification of concrete with ash-containing waste of Dnistrovska PSPS (Ukraine) - Dmytriieva, Nina; Agafonova, Irina; Bostan, Nina (Technology audit and production reserves, 2020)
The object of reseaerch is concrete samples modified with ash-containing fillers and plasticizers. As practice shows, the use of secondary resources is an important issue in the field of construction and entails significant savings. The issue is also considered from the point of view of environmental protection. The study is aimed at determining the effect of modification of concrete with ash-containing waste on the strength characteristics using the example of the hydroelectric power station of the Dnistrovska PSPS (Sokyriany district, Chernivtsi region, Ukraine). The main hypothesis of the study is the assumption that varying components such as fly ash, water glass, and superplasticizers will make it possible to obtain concrete with specified strength characteristics. To achieve the aim, the authors decided to use in the study the superplasticizer SikaPlast-520N and BETO-plast, Portland cement M400 and sands of the quarries of the Parkan and Suklei regions (Moldova). According to the plan of the experiment, studies of the influence of hardening conditions on the structure and properties of modified concrete samples were carried out. Destructive testing of samples was carried out in the laboratory directly on a hydraulic press. The results of experiments without the addition of liquid glass and the introduction of a minimum amount of fly ash and experiments with the introduction of a minimum amount of fly ash and the addition of 3 % water glass are presented. To determine the dynamics of strength gain, tests were carried out on 7, 14 and 28 days. The presented results of the study of the samples on day 7 show a gain of more than 50 % strength. This indicates the possibility of reducing the curing period of structural concrete in the formwork system. A more complete and objective idea of the quality of concrete is possible while taking into account the average strength of concrete and its homogeneity. Today, there is no unified theory that can relate the different properties of cement and filler to the final properties of a composite material. The issue of modifying concrete compositions when using fine aggregate from other quarries requires additional research. At the same time, the results of the experiment show that the use of microfillers based on wastes from the Dnistrovska PSPS provide ample opportunities not only for saving binders, but also for improving the physical, mechanical and operational characteristics of concrete.